Predicting the Stability of Double Fortified Salt by Determining the Coating Quality of the Encapsulated Iron Premix. (31st May 2022) - Siddiqui, Juveria; Modupe, Oluwasegun; Vatandoust, Azadeh; Diosady, Levente L.
Abstract : The technology to simultaneously fortify salt with iron and iodine was developed in Canada and transferred and scaled up in India. The double fortified salt has reached more than 60 million consumers so far. Double fortification of salt is a cost-effective and reliable means of improving iron and iodine deficiencies at a population level. However, high-quality iron premix is essential for the stability of iodine and the program's success. Therefore, we developed a reliable and cost-effective method for premix coating quality evaluation in the field, especially in low-income settings. The integrity and chemical composition of the coating and exposure of iron at the surface (∼10  μ m deep) were determined using scanning electron microscopy and energy-dispersive X-ray spectroscopy to predict the stability of the fortified salt. The phenanthroline colour dropper test was used to test the quality of the double fortified salt by reaction with ferrous iron present on the premix surface. Five iron premix samples were compared. Based on the iron release, coating composition, and the reaction with phenanthroline, Premix-3, and its corresponding DFS, obtained from a local shop in India had the lowest quality among all samples tested. The results of the dropper test corresponded with the analysis using sophisticated analytical tools, confirming it as a simple, reliable, and cost-effective test for iron premix coating quality and integrity. This simple test would be crucial for a successful double fortification program, especially in low-income countries, in predicting iron premix quality, a critical determinant of iodine stability during storage, distribution, and retail. These study results can help governments and NGOs to establish quality standards for iron premix used for salt fortification programs.